Investigation of the Ancient Settlement of Kytaion in 2015–2018: Archaeological Expedition of the State Hermitage Museum - Kattsova, Alexandra (Hyperboreus, 2019)
A survey of the excavations of Kytaion conducted by the archaeological expedition of the State Hermitage Museum in 2015–2018.